Hak-Hak Peserta Didik Perspektif Hasan Langgulung: Kajian Kritis dalam Konteks Pendidikan Islam - Isnaeni Isnaeni; Andi Abdul Hamzah; Nuryamin Nuryamin (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This article examines the concept of student rights in Islamic education from the perspective of Hasan Langgulung's thinking. Using a qualitative descriptive analysis method through literature study, the study in this article aims to analyze Hasan Langgulung's contribution in formulating fundamental rights for students that integrate the principles of educational psychology with Islamic values. The results of the study formulate the fundamental rights of students according to Hasan Langgulung: (1) the right to obtain holistic education, (2) the right to be treated according to individual characteristics, (3) the right to obtain a conducive educational environment, (4) the right to obtain an integrated curriculum, and (5) the right to participate in the learning process. These concepts are relevant to the development of contemporary Islamic education, despite facing implementation challenges including the dichotomy of education, the quality of educators, limited infrastructure, and evaluation systems. This study contributes to the development of a humanistic and holistic Islamic education theory that respects student rights comprehensively.